Effects of p-nonylphenol and resveratrol on body and organ weight and in vivo fertility of outbred CD-1 mice - Boubelik Michael; Buckiova Daniela; Peknicova Jana; Kyselova Vendula (BMC, 2003)
Abstract The aim of this study was to analyse the multigenerational effects of para-nonylphenol (NP) and resveratrol (RES) on the body weight, organ weight and reproductive fitness of outbred CD-1 mice. The data indicate that in male mice, NP had an effect on the weight of selected reproductive organs and the kidneys in the parental (P) generation males. Effects on selected reproductive organs, the liver and kidneys in the F1-generation males were also seen. In females, effects of NP on body weight and kidney weight were seen in the P generation, but no effects on any measured parameter were seen in the F1 generation. RES had no effect on body weight but did have some effect on selected male and female reproductive organs in the P generation. RES altered the spleen and liver weights of P-generation males and the kidney weight of F1-generation males. Acrosomal integrity (using a monoclonal antibody against intra-acrosomal sperm proteins) was assessed for both generations of NP- and RES-treated mice. A significant reduction in acrosomal integrity was seen in both generations of NP-treated, but not in RES-treated, mice. Fewer offspring were observed in the second litter of the F2 generation of mice treated with NP; no similar effect was seen in RES-treated mice. The litter sex ratio was not different from controls. Unlike RES, NP had a negative effect on spermatogenesis and sperm quality with a resultant impact on in vivo fertility.